Factors Influencing Competencies of Nursing Anesthetists at Hospitals under the Ministry of Public Health in Health Region 9 (Nakhon Chai Burin) - Loungmaung, Supattra; Noimuenwai, Premruetai; Srisawas, Karnjana (Journal of The Royal Thai Army Nurses, 2021)
The purposes of this descriptive research were: 1) to study motivation to work, working environment, and competencies of nursing anesthetists at hospitals under the Ministry of Public Health, Health Region 9 Nakhon Chai Burin and 2) to examine the predictor variables: age, income, motivation to work, and working environment on the competencies of nursing anesthetists. The sample included 94 nursing anesthetists in a hospital under the Ministry of Public Health. The research tools composed of questionnaires which composed of 4 sections: 1) general information, 2) motivation to work, 3) working environment, and 4) competencies of nurse anesthetists. The second to the fourth sections of the questionnaires which were validated by 5 experts obtained content validity indexes of 0.98, 0.99, and 0.96 respectively and Cronbach’s alpha reliability coefficients were 0.99, 0.873, and 0.98 respectively. Data were analyzed by descriptive statistics and stepwise multiple regression analysis. The major findings were as follows. 1) Nursing anesthetists rated their overall motivation to work and competencies of nursing anesthetists at the high levels; while, they rated their overall working environment at the moderate level. Lastly, 2) working environment, age, and maintenance factors could predict the competencies of nurse anesthetists, and all of them accounted for 30.40 percent at the significant level of .05